Treatment Outcomes for Single Modality Management of Glomus Jugulare Tumors With Stereotactic Radiosurgery. Issue 9 (October 2016) - Dobberpuhl, Mitchell R.; Maxwell, Stevie; Feddock, Jonathan; St. Clair, William; Bush, Matthew L.
Abstract : Objectives: The objectives were to evaluate the audiological outcomes, response of symptoms, and response of tumor volume in patients with glomus jugulare tumors treated solely with single fraction gamma knife radiosurgery. Study Design: Single institution retrospective review. Setting: Academic, tertiary referral center. Patients: The diagnosis code for glomus jugulare was used to identify patients. Only those who underwent gamma knife radiosurgery were included. Those previously treated with any modality were excluded. A total of 12 patients were included for the tumor response and symptom response data and 7 of those were included in the audiometric analysis. Main Outcomes Measures: Audiometric data at most recent follow-up compared with presentation, subjective improvement in pulsatile tinnitus, and change in tumor volume at most recent follow-up compared with pretreatment. Results: The average time to most recent follow-up was 27.6 months. There was no significant change in pure-tone average or word recognition. Pulsatile tinnitus completely resolved or improved in 80% of patients. Cranial neuropathies were stable or improved. A single patient experienced facial nerve paresis 2 years after treatment, which resolved with steroid treatment. Tumor control was 100% and the average change in tumor volume was a decrease of 37%. Conclusion: Single modality gamma knife radiosurgery treatment of glomus jugulare tumors seems to be safe. Treatment results in decreased tumor volume and improved pulsatile tinnitus in most patients. There was no significant progression of hearing loss after treatment. Lower cranial nerve function remains stable in all patients.